(untitled) (Journal of Science and Technology, 2023)
The research was conducted to determine the physicochemical characteristics of watermelon wine developed from four different Saccharomyces cerevisiae strains (Lalvin EC 1118, Lalvin QA 23, Redstar rouge and Redstar premier classique). The physicochemical characteristics of the treatments determined included pH, titratable acidity, °Brix, and ethanol content. The data obtained were subjected to two-way analysis of variance. The mean pH, titratable acidity, apparent °Brix and ethanol during fermentation ranged between 3.629-3.848, 1.090-1.85%, 17.69-8.13°Brix, and 1.530-7.545ABV% respectively. It was noticed that the fermentation time significantly influenced the physicochemical parameters examined irrespective of the yeast strain used. However, the physicochemical characteristics findings showed that all the yeast strains used were suitable for watermelon wine production.